Perbandingan Kadar Likopen pada Manilkara zapota L., Gnetum gnemon L., Ipomoea batatas L., dan Momordica charantia L. dengan Menggunakan Campuran Solven n-Heksan, Aseton, dan Etanol - R, Nur Syafaatur; R, Panji; W, Reka; M, Rika; NHS, Cikra (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2015)
Lycopene, a member of the carotenoid family of phytochemicals is a lipid soluble antioxidant that is synthesized by many plants and microorganisms but not by animals and human. Lycopene is a natural pigment that imparts red color totomato, guava, rosehip, watermelon, and pink grapefruit. Separation of lycopene from tomato fruit using conventional solvents can be carried out by liquid-liquid extraction method, using a mixture of n-hexane, acetone and ethanol as a solvent. Lycopene assay can be performed using a spectrophotometer method. Sapodilla fruit, leather melinjo, is ripe, and Cilembu sweet potato are some examples of plants that have a yellowish red pigment. This study aimed to investigate and compare the levels of lycopene contained in Cilembu sweet potato (Ipomoea batatas L.), fruit sapodilla (Manilkara zapota L.), bitter melon fruit (Momordica charantia L.), as well as fruit leather melinjo (Gnetum gnemon L.) using conventional solvent extraction method with a mixture of n-hexane, acetone, and ethanol. Data was analyzed by one-way ANOVA, followed by LSD test at 5% level test. The results showed that the concentration of lycopene in the fresh Cilembu sweet potatoes, fresh sapodilla fruit, fresh bitter melon fruit, and fresh fruit peel melinjo is 0.038 ± 0.003 mg/g, 0.085 ± 0.009 mg/g, 0.054 ±0.004 mg/g, 0.015±0.000 mg/g. Fresh sapodilla fruit has the highest lycopene content of 0.085 ±0.009 mg/g.